Application of P-doped C3N4 and PTA heterojunction photocatalyst in photocatalytic degradation of pollutants
Through the preparation of P-doped C3N4 and PTA heterojunction photocatalyst, the problem of poor catalytic performance of existing photocatalysts when degrading pollutants is solved, and efficient degradation of Cr(VI) and tetracycline hydrochloride and good cycle stability are achieved.
Patent Information
- Application Number
- CN202510038429.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
When degrading pollutants, existing photocatalysts have problems such as low reduction potential, severe photogenerated carrier recombination, and reduced hydrophilic sites, resulting in difficult adsorption of pollutants, resulting in poor catalytic performance.
P-doped C3N4 and PTA heterojunction photocatalysts are used to prepare P-doped C3N4 through thermal condensation reaction, and heterojunction is constructed with PTA to improve the light absorption capacity and specific surface area of the photocatalyst and enhance the carrier separation efficiency.
The photocatalytic performance of the photocatalyst is significantly improved, and it can efficiently degrade Cr(VI) and tetracycline hydrochloride, showing excellent activity and cycling stability.
Smart Images

Figure CN119819364A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic degradation of pollutants, and in particular to the application of a P-doped C3N4 and PTA heterojunction photocatalyst in photocatalytic degradation of pollutants. Background Art
[0002] At present, most commonly used semiconductor photocatalysts are inorganic semiconductors, such as bismuth molybdate (Bi2MoO6), cadmium sulfide (CdS), zinc oxide (ZnO), carbon nitride (C3N4), etc. Common heterostructures are often used between inorganic semiconductors. Inorganic semiconductor catalysts usually have high stability and can work under harsh conditions such as high temperature and high pressure, but relatively speaking, it is relatively difficult to regulate the electronic structure. Organic catalysts are another type of attractive catalysts. A key feature of organic photocatalysts with π orbitals is that they are easy to regulate the electronic structure. By adjusting the position and number of functional groups, the photocatalytic properties of organic semiconductors can be effectively adjusted. It is generally believed that photocatalytic activity depends on thermodynamic conditions, charge separation and surface reactions. Organic molecular materials are generally small in size, which can effectively shorten the distance from the generation of photogenerated carriers in the material to their migration to the surface reaction site. Regulating the surface functional groups can change the molecular dipole moment, generate a built-in electric field, and promote the separation of carriers.
[0003] Perylene planar materials have become widely-regarded organic photocatalysts due to their two-dimensional planar π-π stacking electron transfer channels, low production costs, and good light absorption properties. However, their reduction potential is relatively low, and the lack of driving force for photogenerated carriers leads to serious photogenerated carrier recombination. Perylene is highly hydrophobic. During heterogeneous catalysis, the reduction in the number of hydrophilic sites results in the inability of pollutants to be effectively adsorbed on the surface of the material, resulting in poor catalytic performance. Summary of the invention
[0004] Based on the above content, the purpose of the present invention is to provide an application of a P-doped C3N4 and PTA heterojunction photocatalyst in photocatalytic degradation of pollutants. The present invention first uses melamine and ammonium dihydrogen phosphate as raw materials, prepares PCN through two thermal condensation reactions, then hydrolyzes 3,4,9,10-tetracarboxylic anhydride and reacts with acetic acid to prepare PTA, and finally composites PCN and PTA by simple mixing to prepare a P-doped C3N4 and PTA heterojunction photocatalyst. The catalyst can efficiently degrade Cr(VI) and tetracycline hydrochloride.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] An application of a P-doped C3N4 and PTA heterojunction photocatalyst in photocatalytic degradation of pollutants, and a preparation method of the P-doped C3N4 and PTA heterojunction photocatalyst, comprising the following steps:
[0007] After dissolving melamine and ammonium dihydrogen phosphate in solvent 1, drying is performed until solvent 1 is completely removed, and then two thermal condensation reactions are performed to obtain PCN;
[0008] Dispersing 3,4,9,10-tetracarboxylic anhydride in water, and then hydrolyzing it under alkaline conditions to obtain a reaction solution;
[0009] The reaction solution is mixed with an acetic acid solution and stirred for reaction to obtain PTA;
[0010] The PCN and the PTA are uniformly dispersed in the solvent 2, and dried until the solvent 2 is completely removed to obtain the P-doped C3N4 and PTA heterojunction photocatalyst.
[0011] The present invention first performs appropriate P element doping and thermal stripping modification on the sample, and appropriate P doping and stripping can effectively improve the photocatalytic performance of g-C3N4. This is mainly attributed to the fact that the layered structure after stripping can effectively shorten the migration distance of photogenerated carriers, improve the separation efficiency of photogenerated carriers, and significantly improve the catalyst performance.
[0012] Secondly, a non-metallic direct Z-type heterojunction photocatalyst was constructed by combining PTA and PCN. There is π-π stacking between the 2D planar structure of the photocatalyst, which provides favorable conditions for electron migration. At the same time, this structure can increase the specific surface area and provide more surface active sites. In addition, the Z-type charge transfer mechanism retains the strong redox ability and high carrier separation efficiency of photogenerated carriers, which ultimately effectively improves the performance of the photocatalyst. The catalyst exhibits excellent activity and cyclic stability in reducing Cr(VI) ions and degrading tetracycline hydrochloride.
[0013] The present invention discloses the following technical effects:
[0014] The construction of the heterojunction in the present invention effectively broadens the light absorption range of the catalyst and enhances its light absorption capacity. In addition, the construction of the heterojunction increases the specific surface area of the material, providing more reaction sites for the reaction. At the same time, the introduction of PTA introduces hydroxyl functional groups on the surface, increasing the hydrophilicity of the material. It promotes the photocatalytic degradation of Cr(VI) and tetracycline hydrochloride. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 The water contact angles of (a) PTCDA and (b) PTA in Example 1.
[0017] Figure 2 (a) XRD spectra and (b) FT-IR spectra of the photocatalysts prepared in Examples 1 to 5.
[0018] Figure 3 These are SEM images of (a) PCN, (b) PTA and (c) 6:4 PCN / PTA in Example 4.
[0019] Figure 4 In Example 4, (a) TEM photo of PCN, (b) HRTEM photo of PCN, (c) TEM photo of PTA, (d) HRTEM photo of PTA, (e) TEM photo of 6:4PCN / PTA sample, and (f) HRTEM photo of 6:4PCN / PTA sample.
[0020] Figure 5 These are the HADDF STEM image and EDS distribution diagram of 6:4PCN / PTA in Example 4, where (a) HADDF STEM image, (b) P element, (c) C, (d) N, and (e) O.
[0021] Figure 6 This is the XPS survey spectrum of PTA and 6:4PCN / PTA samples in Example 4.
[0022] Figure 7 These are the XPS spectra of PCN, PTA and 6:4PCN / PTA samples in Example 4, where (a) C 1s, (b) N 1s, (c) O 1s, and (d) P 2p.
[0023] Figure 8 (a) Adsorption of Cr(VI) of different photocatalysts in the effect verification example, (b) photocatalytic reduction of Cr(VI), (c) kinetic curve of degradation of Cr(VI), (d) adsorption of tetracycline hydrochloride, (e) photocatalytic degradation of tetracycline hydrochloride, and (f) kinetic curve of degradation of tetracycline hydrochloride.
[0024] Fig. 9 In the effect verification example, (a) 6:4PCN / PTA condition control comparison experiment, (b) the degradation effect of PCN, PTA, and 6:4PCN / PTA on different substances under 20 minutes of light, (c) the free radical capture of 6:4PCN / PTA in the degradation of tetracycline hydrochloride, and (d) the cyclic stability of 6:4PCN / PTA.
[0025] Fig.10These are the nitrogen adsorption-desorption curves of (a) PCN, (b) PTA and (c) 6:4PCN / PTA in the effect verification example, and the BJH method (desorption) differential integral pore volume pore size distribution curves of (d) PCN, (e) PTA and (f) 6:4PCN / PTA.
[0026] Fig.11 For the effect verification example, (a) UV-visible diffuse reflectance spectra of different catalysts, (b) Tauc-plot of PCN and PTA, (c) VB-XPS spectra of PCN and PTA, and (d) band structure diagram of PCN and PTA. DETAILED DESCRIPTION
[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0028] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0029] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0030] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0032] In the present invention, room temperature means 20-30°C.
[0033] The present invention provides an application of a P-doped C3N4 and PTA heterojunction photocatalyst in photocatalytic degradation of pollutants. The preparation method of the P-doped C3N4 and PTA heterojunction photocatalyst comprises the following steps:
[0034] After dissolving melamine and ammonium dihydrogen phosphate in solvent 1, drying is performed until solvent 1 is completely removed, and then two thermal condensation reactions are performed to obtain PCN;
[0035] Dispersing 3,4,9,10-tetracarboxylic anhydride in water, and then hydrolyzing it under alkaline conditions to obtain a reaction solution;
[0036] The reaction solution is mixed with an acetic acid solution and stirred for reaction to obtain PTA;
[0037] The PCN and the PTA are uniformly dispersed in the solvent 2, and dried until the solvent 2 is completely removed to obtain the P-doped C3N4 and PTA heterojunction photocatalyst.
[0038] In some embodiments of the present invention, the solvent 1 is water; the usage ratio of melamine and diammonium phosphate is: the molar ratio of P:C3N4 is 0.1% to 3%.
[0039] In some embodiments of the present invention, the usage ratio of melamine and diammonium phosphate is: the molar ratio of P:C3N4 is 0.5%.
[0040] P atoms tend to form substitutional doping in the lattice. The introduction of P atoms will cause lattice distortion, resulting in electron redistribution, destruction of the interlayer large π bonds, and weakening of the material's electron transport capacity. Therefore, excessive P doping has a negative effect on the photocatalytic performance of the material. In order to ensure the catalytic performance of the obtained photocatalyst, the present invention limits the amount of melamine and diammonium phosphate to the above parameters.
[0041] The present invention does not specifically limit the amount of solvent 1, as long as it can completely dissolve melamine and diammonium phosphate. The present invention does not specifically limit the drying method, temperature and time, as long as the solvent 1 can be completely removed, for example: drying in a water bath at 80°C until the solvent 1 is completely removed.
[0042] In some embodiments of the present invention, the two thermal condensation reactions are specifically: first, the temperature is raised to 540-560°C at a heating rate of 4-6°C / min, and the temperature is kept for 2-3 hours. After the temperature is kept, it is cooled to room temperature, the reaction product is ground, and then the ground powder is heated to 540-560°C at a heating rate of 4-6°C / min, and the temperature is kept for 3-4 hours. The present invention regulates the morphology of PCN through two thermal condensation treatments, so that it is peeled into nanosheets.
[0043] The reason why the present invention limits the parameters of the two thermal condensations to the above range is that the heating rate is a key factor in the performance of the synthesized C3N4 material. A slower heating rate helps to achieve a higher degree of nitridation, uniform particle size, higher crystallinity and less carbon residue, thereby obtaining C3N4 with higher purity and better performance. Although rapid heating can shorten the reaction time, it may lead to problems such as incomplete nitridation, excessive carbon residue, uneven particles, disordered structure, etc., affecting the performance of the final material.
[0044] In some embodiments of the present invention, the mass volume ratio of the 3,4,9,10-tetracarboxylic anhydride to water is 0.2 g:600 mL. The present invention does not specifically limit the method of dispersing 3,4,9,10-tetracarboxylic anhydride (PTCDA) into water, and conventional technical means of those skilled in the art can be used, such as ultrasonic dispersion.
[0045] In some embodiments of the present invention, the alkaline condition is to add potassium hydroxide to the reaction system; the mass ratio of potassium hydroxide to PTCDA is 2:1.
[0046] In some embodiments of the present invention, the reaction temperature of the hydrolysis is 50° C. and the reaction time is 30 min.
[0047] In some embodiments of the present invention, the concentration of the acetic acid solution is 1% v / v; and the volume ratio of the reaction solution to the acetic acid solution is 3:1.
[0048] In some embodiments of the present invention, the stirring reaction is carried out at room temperature for 2 hours.
[0049] In some embodiments of the present invention, after the stirring reaction is completed, the steps of filtering, washing and drying the filtered product are also included.
[0050] In some embodiments of the present invention, the solvent 2 is ethanol; the mass ratio of the PCN to the PTA is (1-9):1.
[0051] In some embodiments of the present invention, the mass ratio of the PCN to the PTA is 9:1, 8:2, 7:3, 6:4, or 5:5.
[0052] In some embodiments of the present invention, the pollutants are Cr(VI) and tetracycline hydrochloride.
[0053] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0054] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0055] Example 1
[0056] A P-doped C3N4 and PTA heterojunction photocatalyst, the preparation steps are as follows:
[0057] Step 1: Prepare P-doped C3N4 photocatalyst by thermal condensation method to obtain PCN:
[0058] 1) Weigh melamine and ammonium dihydrogen phosphate (according to a P:C3N4 molar ratio of 0.5%), dissolve them in 60 mL of distilled water in a beaker, dry them in a water bath at 80°C until the water in the beaker is evaporated and evenly dispersed, then dry them in an oven at 80°C for 12 h, transfer them to a muffle furnace with a crucible and heat them at a heating rate of 5°C / min, a target temperature of 550°C, and a holding time of 2 h. After natural cooling, take them out and grind them into powder to obtain block C3N4.
[0059] 2) The block C3N4 was heated again in a muffle furnace at a heating rate of 5°C / min, a target temperature of 550°C, and a holding time of 4h. The obtained sample was 0.5% PCN.
[0060] Step 2, preparation of PTA from PTCDA:
[0061] 0.2g PTCDA was added to 600mL deionized water, dispersed by ultrasonication for 20min, and then 0.4g KOH was added and the mixture was heated in a water bath at 50℃ for 30min to form a yellow-green transparent solution A. 2mL acetic acid was diluted to 200mL with deionized water and recorded as solution B. After solution A was cooled to room temperature, solution A was mixed with solution B and stirred for 2h. Filtered and washed with deionized water until the filtrate was neutral. The sample was collected, dried at 60℃ for 12h, and ground to obtain dark red PTA nanosheets.
[0062] Step 3, compounding PCN and PTA nanosheets by simple mixing method:
[0063] Weigh 0.9 g of 0.5% PCN and 0.1 g of PTA nanosheets, add them to a beaker containing 40 mL of ethanol, ultrasonicate at 60 kHz for 30 min, stir for 5.5 h, dry the water in a water bath at 80 °C, collect the catalyst, and dry it again to obtain a P-doped C3N4 and PTA heterojunction photocatalyst (denoted as 9:1PCN / PTA).
[0064] Example 2
[0065] The difference from Example 1 is that 0.9 g 0.5% PCN and 0.1 g PTA nanosheets are replaced by 0.8 g 0.5% PCN and 0.2 g PTA nanosheets, and the remaining steps and parameters are the same as those of Example 1. The obtained P-doped C3N4 and PTA heterojunction photocatalyst is recorded as 8:2PCN / PTA.
[0066] Example 3
[0067] The difference from Example 1 is that 0.9 g 0.5% PCN and 0.1 g PTA nanosheets are replaced by 0.7 g 0.5% PCN and 0.3 g PTA nanosheets, and the remaining steps and parameters are the same as those of Example 1. The obtained P-doped C3N4 and PTA heterojunction photocatalyst is recorded as 7:3PCN / PTA.
[0068] Example 4
[0069] The difference from Example 1 is that 0.9 g 0.5% PCN and 0.1 g PTA nanosheets are replaced by 0.6 g 0.5% PCN and 0.4 g PTA nanosheets, and the remaining steps and parameters are the same as those of Example 1. The obtained P-doped C3N4 and PTA heterojunction photocatalyst is recorded as 6:4PCN / PTA.
[0070] Example 5
[0071] The difference from Example 1 is that 0.9 g 0.5% PCN and 0.1 g PTA nanosheets are replaced by 0.5 g 0.5% PCN and 0.5 g PTA nanosheets, and the remaining steps and parameters are the same as those of Example 1. The obtained P-doped C3N4 and PTA heterojunction photocatalyst is recorded as 5:5 PCN / PTA.
[0072] Effect verification example
[0073] 1. Structural morphology analysis
[0074] Hydroxyl groups are hydrophilic groups. As the number of hydroxyl groups in the catalyst increases, the contact angle decreases. First, the contact angle test ( Figure 1 In (a)(b), the introduction of hydroxyl groups in the sample was confirmed. The contact angle of PTCDA was 63.481°, and the contact angle of PTA was reduced to 34.143°, indicating that hydroxyl groups were successfully introduced into PTCDA and PTA was successfully synthesized. In the heterogeneous catalytic process, the stronger the hydrophilicity, the easier it is to contact the pollutants in the aqueous solution, which is beneficial to the photocatalytic process. The crystal structure of the sample was determined by X-ray diffraction test (XRD). Figure 2As shown in (a), the position of the strongest XRD diffraction peak of PTA is at 22.78°, corresponding to the (021) crystal plane of PTA and the π-π stacking of the perylene plane. The peaks of 12.8° and 27.5° in PCN correspond to its (100) and (002) crystal planes, respectively. The characteristic diffraction peak of the PCN (100) crystal plane in the PCN / PTA composite sample gradually weakens with the increase of the amount of PTA introduced, and is finally merged by the diffraction peak of PTA at 12.3°. With the increase of the amount of PTA introduced, the diffraction peak corresponding to the (021) crystal plane of PTA becomes increasingly obvious, while the diffraction peak of the (002) crystal plane of PCN gradually weakens and shifts to a lower angle, which may be attributed to the π-π stacking between PCN and PTA. This result is consistent with the successful construction of the heterojunction.
[0075] To further verify the successful construction of the heterojunction, the functional groups and chemical bond states of the catalyst were analyzed by infrared spectroscopy. Figure 2 As shown in (b), PTA exhibits multiple split peaks at 1770 cm -1 The absorption peak at 1300 cm-1 can be attributed to the C=O double bond of the carboxyl group in perylenetetracarboxylic acid, and the vibration of the hydroxyl group can be found at 1300 cm-1. -1 Observed at 1600cm -1 The vibration at 811 cm -1 The vibration at can be attributed to the out-of-plane stretching vibration of the benzene ring. It can be seen that with the introduction of PTA, the vibration of the characteristic peak of PTA gradually increases, and the characteristic peak of PCN gradually weakens. This reflects the successful compounding of semiconductors and the changes in the content of each component in the heterojunction.
[0076] The morphology of the samples was characterized by SEM and TEM. Figure 3 As shown in the figure, both PCN and PTA exhibit nanosheet structures. The size of PTA nanosheets is relatively small compared to PCN. After mixing, PTA is dispersed on PCN nanosheets, and an obvious sheet stacking structure can be observed. Large-area sheet stacking provides favorable conditions for possible π-π stacking electron migration. TEM tests further confirmed this result, such as Figure 4 As shown, it can be seen that both PCN and PTA exhibit nanosheet structures. The TEM image of 6:4PCN / PTA shows a typical ultra-thin nanosheet structure, proving the construction of face-to-face stacked two-dimensional van der Waals heterojunction. Since PCN and PTA are both amorphous materials, no lattice fringes were observed in the HRTEM images of PCN, PTA and 6:4PCN / PTA. By further performing HADDF and EDX elemental surface scanning analysis on the 6:4PCN / PTA sample, as shown in Figure 5As shown, the uniform distribution of P, C, N, and O elements on the sample surface can be seen, indicating the uniform recombination of PCN and PTA. This result proves the synthesis of the heterojunction.
[0077] The surface chemical state and binding energy were analyzed by XPS spectroscopy. Figure 6 The XPS survey spectrum shows the elements contained in PCN, PTA, and 6:4PCN / PTA. It can be seen that the peak signals of P, C, N, and O are observed simultaneously in PCN, indicating the successful doping of P, among which the O signal can be attributed to the O defect formed by the adsorption of O in the air during the sintering process. Only the characteristic peaks of C, N, and O elements were observed in the survey spectrum of 6:4PCN / PTA. It may be due to the low P content. After the heterojunction is constructed, PTA covers the surface of PCN, and the P element content exposed on the catalyst surface is low, so the P signal is not detected. The presence of P was observed in the subsequent XPS element high-resolution spectrum, indicating the successful construction of the heterojunction. Figure 7 (a) shows the high-resolution C1s spectrum of the catalyst. PCN exhibits two peaks at 284.80 and 288.08 eV. The peak at 284.80 eV comes from the CC or C=C bond of amorphous carbon, and the peak at 288.08 originates from the NC=N binding state of the triazine structure in PCN. The peak at 288.98 eV in PTA can be attributed to the planar large π bond on the benzene ring in the perylene structure. N 1s spectrum ( Figure 7 The two peaks of 398.57 and 400.31 eV in (b) correspond to the CN=C and N–H binding states in PCN. Figure 7 The fitting peaks in (c) are located at 531.60 and 533.51 eV, corresponding to C=O in perylene tetracarboxylic acid and OH group in carboxyl group, respectively. The binding energy of 133.55 eV in the P 2p high-resolution spectrum of PCN corresponds to PN / P=N formed by the C site in the P-substituted triazine structure. It can be found that the binding energy of C, N, O, P and other elements of 6:4PCN / PTA has moved to higher binding energy compared with PCN, and the binding energy has moved to lower binding energy compared with PTA, indicating that the construction of heterojunction makes electrons flow from PCN to PTA. The ratio of the amount of each element in the sample obtained by XPS is shown in Table 1.
[0078] Table 1 The actual content ratio of each element in different samples
[0079]
[0080] 2. Photocatalytic performance evaluation
[0081] The photocatalytic performance of the catalyst was evaluated by degradation of tetracycline hydrochloride and Cr(VI) under visible light (λ>420nm). Figure 8 As shown in (a) and (d), the adsorption and desorption equilibrium time of the catalyst and tetracycline hydrochloride or Cr(VI) under dark conditions was measured before irradiation. After reaching the adsorption-desorption equilibrium, the illumination was turned on, and it was found that the pollution concentration in the mixture solution gradually decreased. The construction of the heterojunction significantly improved the performance of the catalyst. Under 20 minutes of illumination, the degradation rates of Cr(VI) by PCN and PTA were 45% and 40%, and the degradation rates of tetracycline hydrochloride were 42% and 55%. Heterojunctions with different mass ratios showed improved photocatalytic effects. With the increase in the amount of PTA introduced, the catalyst performance first increased and then decreased, and 6:4PCN / PTA showed the best photocatalytic effect. Under 20 minutes of illumination, the degradation rate of Cr(VI) increased to 57%, and the degradation rate of tetracycline hydrochloride increased to 78%. The pseudo-first-order reaction kinetic constants of the reaction were calculated, as shown in Figure 8 As shown in (c) and (f), the degradation rate of Cr(VI) by 6:4PCN / PTA is 0.0340min. -1 , respectively PCN(0.0232min -1 ) and PTA(0.0184min -1 ) are 1.47 and 1.84 times.
[0082] In order to further evaluate the photocatalytic performance of the heterojunction and explore the active substances in the degradation process, controlled variable comparison experiments were carried out on illumination and catalyst addition. In the absence of catalyst or illumination, the concentration changes of Cr(VI) and tetracycline hydrochloride were negligible, indicating that Cr(VI) and tetracycline hydrochloride were relatively stable under illumination and not easily degraded. Under the condition of adding catalyst but not adding illumination, the concentration of Cr(VI) decreased by 14% and tetracycline hydrochloride decreased by 5.7%, which may be due to the adsorption of the catalyst. Under the condition of adding catalyst and illumination at the same time, the concentration of pollutants decreased significantly after 20 minutes. It can be seen that the degradation of pollutants is mainly due to the photocatalytic degradation of the catalyst. In addition, 6:4PCN / PTA was also used to degrade rhodamine B, such as Fig. 9 As shown in (b), 6:4PCN / PTA has good universality and has good degradation effects on common pollutants such as Cr(VI), tetracycline hydrochloride, and rhodamine B. Compared with the original sample, the degradation effect of the heterojunction on various pollutants has been significantly improved. In order to study the contribution of active substances in the process of 6:4PCN / PTA photocatalytic degradation of tetracycline hydrochloride, we conducted an active substance capture experiment. Superoxide radicals (·O2 - ), hole (h +) and hydroxyl radicals (·OH) were quenched with 1 mmol TEMPO, 1 mmol potassium iodide (KI) and 1 mL isopropanol (IPA), respectively. Fig. 9 As shown in (c), when TEMPO was added, the degradation of tetracycline hydrochloride was severely inhibited, indicating that ·O2 - is the main active substance. When KI and IPA were added, the degradation of tetracycline hydrochloride was slightly inhibited, indicating that h + and ·OH are not the main active species. Also attributed to the good interfacial contact between PCN and PTA, 6:4PCN / PTA exhibits good cycling stability, such as Fig. 9 As shown in (d), the efficiency of the catalyst in degrading tetracycline hydrochloride is relatively stable within 5 cycles.
[0083] 3. Specific surface area analysis
[0084] Considering the possible influence of specific surface area on the photocatalytic effect, nitrogen adsorption-desorption test was carried out on the samples to analyze the specific surface area of the samples. Fig.10 As shown in the figure, the specific surface areas of samples PCN, PTA and 6:4PCN / PTA were 8.85, 5.16 and 14.51 m 2 / g, and the pore volumes are 0.12, 0.05 and 0.12mL / g, respectively. According to the IUPAC classification, these three samples all belong to type IV isotherms. Compared with the original samples PCN and PTA, the 6:4PCN / PTA sample exhibits a larger specific surface area, which may be one of the reasons for the improved photocatalytic performance of the heterojunction. A large specific surface area means a large interface contact, which provides sufficient reaction sites for the migration of photogenerated carriers and interfacial reactions, and is beneficial to the photocatalytic effect. The average pore diameters are 50.69, 41.89, and 32.85nm, respectively. The reduced pore size distribution side confirms the uniform distribution of PTA on the PCN surface.
[0085] 4. Optical absorption and band position analysis
[0086] In order to explore the effect of the introduction of PTA on the optical absorption capacity of the heterojunction, the light absorption capacity of the sample in the range of 300 to 800 nm was measured by ultraviolet visible diffuse reflectance spectroscopy (UV-vis DRS). Fig.11As shown in (a), the absorption edge of PCN is near 470nm. With the introduction of PTA, the absorption range of the heterojunction increases significantly, from 470nm to 660nm. According to the tauc-plot formula, the band gap of PCN is 2.66eV, and the band gap of PTA is 1.98eV. The construction of the heterojunction effectively improves the light absorption performance of the catalyst. The 9:1PCN / PTA sample with a small amount of PTA added shows a significant improvement in light absorption performance. Combined with the valence band position obtained by VB-XPS test, the following is drawn: Fig.11 Schematic diagram of the energy band structure shown in (d). The valence band position of PCN is 1.54eV, the conduction band position is -1.12eV, and the valence band position of PTA is 0.82eV, and the conduction band position is -1.16eV. The staggered energy band structure meets the prerequisite for the formation of a Z-type heterojunction. Combined with the electron flow direction inferred from the XPS element binding energy shift, it can be seen that a Z-type heterojunction is formed between PCN and PTA.
[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. Application of a P-doped C3N4 and PTA heterojunction photocatalyst in photocatalytic degradation of pollutants, characterized in that: The preparation method of the P-doped C3N4 and PTA heterojunction photocatalyst comprises the following steps: After dissolving melamine and ammonium dihydrogen phosphate in solvent 1, drying is performed until solvent 1 is completely removed, and then two thermal condensation reactions are performed to obtain PCN; Dispersing 3,4,9,10-tetracarboxylic anhydride in water, and then hydrolyzing it under alkaline conditions to obtain a reaction solution; The reaction solution is mixed with an acetic acid solution and stirred for reaction to obtain PTA; The PCN and the PTA are uniformly dispersed in the solvent 2, and dried until the solvent 2 is completely removed to obtain the P-doped C3N4 and PTA heterojunction photocatalyst.
2. The use of the P-doped C3N4 and PTA heterojunction photocatalyst in photocatalytic degradation of pollutants according to claim 1, characterized in that: The solvent 1 is water; the usage ratio of melamine and diammonium phosphate is: the molar ratio of P:C3N4 is 0.1% to 3%.
3. The use of the P-doped C3N4 and PTA heterojunction photocatalyst in photocatalytic degradation of pollutants according to claim 1, characterized in that: The two thermal condensation reactions are specifically as follows: firstly, the temperature is increased to 540-560°C at a heating rate of 4-6°C / min, and the temperature is kept for 2-3 hours. After the temperature is kept, the temperature is cooled to room temperature, the reaction product is ground, and then the ground powder is heated to 540-560°C at a heating rate of 4-6°C / min, and the temperature is kept for 3-4 hours.
4. The use of the P-doped C3N4 and PTA heterojunction photocatalyst in photocatalytic degradation of pollutants according to claim 1, characterized in that: The mass volume ratio of the 3,4,9,10-tetracarboxylic anhydride to water is 0.2 g:600 mL; the reaction temperature of the hydrolysis is 50° C., and the reaction time is 30 min.
5. The use of the P-doped C3N4 and PTA heterojunction photocatalyst in photocatalytic degradation of pollutants according to claim 1, characterized in that: The concentration of the acetic acid solution is 1% v / v; the volume ratio of the reaction solution to the acetic acid solution is 3:
1.
6. The use of the P-doped C3N4 and PTA heterojunction photocatalyst in photocatalytic degradation of pollutants according to claim 1, characterized in that: The stirring reaction was carried out at room temperature for 2 hours.
7. The use of the P-doped C3N4 and PTA heterojunction photocatalyst in photocatalytic degradation of pollutants according to claim 1, characterized in that: After the stirring reaction is completed, the steps of filtering, washing and drying the filtered product are also included.
8. The use of the P-doped C3N4 and PTA heterojunction photocatalyst in photocatalytic degradation of pollutants according to claim 1, characterized in that: The solvent 2 is ethanol; the mass ratio of the PCN to the PTA is (1-9):
1.
9. The use of the P-doped C3N4 and PTA heterojunction photocatalyst in photocatalytic degradation of pollutants according to claim 1, characterized in that: The pollutants are Cr(VI) and tetracycline hydrochloride.